100 texture evolution in bcc Fe sheets - Computational design and experiments. (March 2016) - Kim, Kyeong-Min; Kim, Hyun-Kyu; Park, Jun Young; Lee, Jae Sang; Kim, Seong Gyoon; Kim, Nack Joon; Lee, Byeong-Joo
Abstract: A computational and experimental study has been carried out to produce highly value-added 100 textured steel sheets. This study is based on an idea that an anisotropic surface segregation tendency of impurity atoms would cause an inversion of relative surface energy between 110 and 100 surfaces in bcc Fe and may induce the formation of 100 texture in steel sheets during grain coarsening. A phase field model that can consider surface segregation of impurity atoms (and resultant decrease of surface energy) and grain growth simultaneously is newly developed. The phase field model and surface property data obtained from an atomistic approach are used to simulate grain coarsening behavior of phosphorus-containing iron and to find an optimum process condition that can induce the 100 texture in steel sheets. The phase field simulation indicates that the surface segregation and resultant change in the relative difference in surface energy should be accomplished before the start of grain coarsening for an effective formation of the 100 texture. A strong 100 texture is indeed generated experimentally in phosphorus-containing bcc Fe-3.5wt% Si steel sheets through a two-step annealing process, one at a relatively low temperature where only surface segregation can occur but not the grain coarsening and the other at a relatively high temperature where the grain coarsening can also occur. Graphical abstract: